2017
DOI: 10.1248/yakushi.16-00077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk Factors for Severe Oral Mucositis in Head and Neck Cancer after Chemoradiotherapy with S-1

Abstract: Radiotherapy (RT) and chemoradiotherapy (CRT) is widely accepted as the standard treatment for head and neck cancer (HNC). Oral mucositis (OM) often develops as an adverse reaction in HNC patients that receive RT or CRT involving S-1. However, little is known about the risk factors for OM in HNC patients. We retrospectively evaluated patients' pre-treatment clinical data in order to identify the risk factors for severe OM in HNC patients that are treated with RT or CRT involving S-1. We analyzed the cases of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We previously demonstrated that concurrent chemotherapy was identified as a significant, independent risk factor for the severity of OM 16 . Hata et al reported that 5‐FU was related to worse OM 5 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We previously demonstrated that concurrent chemotherapy was identified as a significant, independent risk factor for the severity of OM 16 . Hata et al reported that 5‐FU was related to worse OM 5 .…”
Section: Discussionmentioning
confidence: 91%
“…We previously demonstrated that concurrent chemotherapy was identified as a significant, independent risk factor for the severity of OM. 16 Hata et al reported that 5‐FU was related to worse OM. 5 This study also revealed a relationship between cumulative radiation dose, even lower doses, and the development of OM in patients with HNC during RT.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the P values of OM severity there was no significant difference between the two groups. Figures (3,4) show dry ulcerated borders of the mouth, mucosal erythema, ulcers and atrophic and coated tongue at day 42 for patients from the two groups. 2-Regarding VAS Table 3, figure 2 show comparison between the two groups using VAS.…”
Section: Resultsmentioning
confidence: 99%
“…Although both treatments have good cure rates during the early stages, these treatments can lead to functional impairments (3). Radiotherapy has irreversible side effects on the oral mucosa such as OM, xerostomia along with added risk of osteoradionecrosis (4,5). OM has impacts on the quality of life, morbidity and mortality (6).…”
Section: Introductionmentioning
confidence: 99%
“…Severe oral mucositis requires immediate treatment, requiring dose reduction, or interruption of chemotherapy, affecting the patient's prognosis and quality of life and generating a strong economic impact associated with hospitalization support [6]. Some risk factors for oral mucositis have been described, such as age and gender [12], time of diagnosis, previous history of [13], and some speci c drugs are more strongly associated with oral mucositis than others [14]. Additionally, numerous ways to decrease the incidence of oral mucositis [15], such as lowintensity laser therapy [16], have been tested.…”
Section: Introductionmentioning
confidence: 99%